Leveraging machine learning techniques for image classification and revealing social media insights into human engagement with urban wild spaces - Haider Khalid; Marcus J. Collier (Scientific Reports)
Abstract In recent years, machine learning models have exhibited excellent performance and far-reaching impact across domains such as fraud detection in finance, recommendation systems in e-commerce, medical imaging in healthcare, agricultural forecasting, social engagement, image classification, sentiment analysis in social media network analysis. This research explores how advanced machine learning techniques, leveraging social media data for image classification, can be used to gain deeper insights into public engagement with urban wild spaces. The study follows a two-step methodology: first, scraping image data from Instagram, Facebook, and Flickr using hashtag-based techniques focused on urban wild spaces; second, developing an experimental pipeline using Convolutional Neural Networks (CNN), Density-Based Spatial Clustering of Applications with Noise (DBSCAN), and Convolutional Autoencoders (CAE) to classify and evaluate the scrapped social media data. Evaluation was based on precision, recall, F-measure, and accuracy metrics. Across all three platforms, CAE consistently outperformed CNN and DBSCAN, achieving peak accuracies of 74.8% on Flickr, 70.4% on Instagram, and 62.9% on Facebook, along with balanced F-measures and high recall. CNN showed the highest precision, reaching 98.4% on Flickr, while DBSCAN provided moderate results. These findings show that machine learning effectively filters noisy data and reveals how people engage with urban wild spaces, offering valuable insights for urban planning and ecology.